The ‘Family Project’: investigating multi-belief peer learning in two Irish primary schools - Malone, Tara (British Journal of religious education, 2021)
In 2007, a new model of state-run primary schools was established in Ireland in response to growing pluralism in this country. These are publicly-managed, multidenominational schools with the Irish state, through the Education and Training Boards (ETB) as their patron. School ethos is inclusive, striving to ensure that beliefs of all children are respected and celebrated. There are currently twenty-three schools in this sector. A multi-belief curriculum has been written for schools; one methodology employed, ‘the Family Project’ is the focus of this research. It aims to encourage students to engage in conversation with their families about specific themes being explored in school, and to complete their projects at home. Students then present Family Projects to peers in school, educating one another about how they express or live out their beliefs. This mixed-methods study explores students’ views on how they feel about sharing religious or secular beliefs with peers and about learning from peers. Using questionnaires and focus groups with children in 5th class (10–12 years) significant insights are revealed. Students reported positive attitudes towards listening to each other’s beliefs but ambivalence about presenting beliefs. They highlighted the importance of a safe space being created for the sharing of beliefs.